The growth, aboveground biomass, crown development, and leaf characteristics of three Eucalyptus species at initial stage of planting in Jepara, Indonesia - PANDU YUDHA ADI PUTRA WIRABUANA; Syamsu Alam; Jeriels Matatula; Moehar Marghiy Harahap; Yusanto Nugroho; Fahmi Idris; Alnus Meinata; Dewa Ayu Sekar (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wirabuana PYAP, Alam S, Matatula J, Harahap MM, Nugroho Y, Idris F, Meinata A, Sekar DA. 2021. The growth, aboveground biomass, crown development, and leaf characteristics of three Eucalyptus species at initial stage of planting in Jepara, Indonesia. Biodiversitas 22: 2859-2869. Industry development, climate change mitigation and renewable energy currently become the most essential challenge in tropical forest management, primarily in Indonesia. The existence of tropical forests is not only managed to maintain the stability of wood supply for commercial industries but also to reduce greenhouse gas emissions in the atmosphere and to generate energy alternatives from tree biomass. To answer this challenge, the development of fast-growing species like eucalyptus can become a good solution. However, the productivity of eucalyptus depends on its adaptability to the site condition. Therefore, understanding site-species interaction becomes the fundamental requirement before planted on a large scale. This study aimed to evaluate the initial performance of eucalyptus species developed in Jepara. An experiment consisted of three different eucalyptus species, i.e., E. alba, E. pellita, and E. urophylla, was established using a randomized complete block design. Sixteen parameters were selected to assess the eucalyptus performance, including survival, height, diameter, biomass accumulation (stem, branches, foliage, and total aboveground), crown length, crown radius, crown projection area, crown ratio, individual leaf area, individual leaf dry weight, specific leaf area, leaf mass area, and leaf area index. The comparison of the mean of tree attributes from each species was examined using ANOVA, followed by HSD Tukey. Results showed that all measured parameters indicated a significant difference among the three species (p<0.05), except for survival, foliage biomass, and crown ratio (p>0.05). The preliminary performance of E. pellita was relatively better than the other two species, mainly related to height (3.00±0.21 m), total aboveground biomass (49.86±3.60 kg ha-1), crown projection area (2.68±0.27 m2 ), and leaf area index (5.76±0.44). Our study concluded the initial performance of E. pellita in Jepara was substantially superior to E. alba and E. urophylla. Nevertheless, continuous evaluation is needed to monitor the consistent performance of those species in the study area.